2022
DOI: 10.3389/fpls.2022.980745
|View full text |Cite
|
Sign up to set email alerts
|

Combined physiological and transcriptome analysis revealed the response mechanism of Pogostemon cablin roots to p-hydroxybenzoic acid

Abstract: Pogostemon cablin (patchouli) cultivation is challenged by serious soil sickness, of which autotoxins accumulation is a major cause. p-hydroxybenzoic acid (p-HBA) is one of the main autotoxins of patchouli. However, the molecular mechanism underlying the response of patchouli to p-HBA remains unclear. In this study, RNA-sequencing combined with physiological analysis was used to monitor the dynamic transcriptomic and physiological changes in patchouli seedlings 0, 6, 12, 24, 48, and 96 h after p-HBA treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…RNA-seq has been utilized as a prospective method to investigate the intricate molecular pathways linked with a given phenotype ( Shen et al., 2020 ; Ji et al., 2022 ; Yan et al., 2022 ). Global differential gene expression profiling in the overexpressing soybean lines revealed that GmWRKY172 regulates multiple biological pathways.…”
Section: Discussionmentioning
confidence: 99%
“…RNA-seq has been utilized as a prospective method to investigate the intricate molecular pathways linked with a given phenotype ( Shen et al., 2020 ; Ji et al., 2022 ; Yan et al., 2022 ). Global differential gene expression profiling in the overexpressing soybean lines revealed that GmWRKY172 regulates multiple biological pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Reads with a low quality (Q < 20) or containing more than 10% N bases were excluded using Trimmomatic-0.39.jar ( Yan et al., 2022 ). The P. cablin genome sequence, including the coding DNA sequence (CDS), protein sequences and GFF3 files, was downloaded from the figshare database ( https://figshare.com/ ).…”
Section: Methodsmentioning
confidence: 99%
“…The transcript abundance was determined using RSEM ( Li et al., 2011 ). DEGs (log2FC > 2 or < -2 and p value < 0.001) were screened using DESeq2 version 2.10 ( Yan et al., 2022 ). Correlations were determined by calculating Pearson’s correlation coefficient (r).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found that the deterioration of soil physiochemical properties, the accumulation of allelochemicals, and the imbalance of microbial communities are the main causes of continuous cropping obstacles [12][13][14]. Among them, p-hydroxybenzoic acid (p-HBA) has been proved as a key allelochemical inducing the occurrence of P. cablin continuous cropping obstacles [15,16]. However, how does p-HBA induce the occurrence of P. cablin continuous cropping obstacles?…”
Section: Introductionmentioning
confidence: 99%